After sound toward a critical music - Barrett, G. Douglas ca. 20./21. Jh (Bloomsbury Academic, 2016)
"After Sound examines contemporary art practices that reconceive music beyond the limitation of sound. Coining the term "critical music," it examines a diverse collection of art projects which intervene into specific political and philosophical conflicts by exploring music's unique historical forms"...